The Future of African-European Relations
X, 494 p. 22 illus., 15 illus. in color.
Keywords: This book explores the future of African-European relations with a focus on achieving equity in a global context. Drawing on the expertise of policymakers, institutional stakeholders, scholars, and practitioners from both the global south and the global north, this contributed book offers unique insights into successful cooperation strategies between Africa and Europe. By offering case studies and clear perspectives, the book covers topics such as the implementation of public policies, the role of culture and languages, judicial independence, e-governance, technical cooperation and project management, energy crisis, economic growth, and global health. Moving beyond conventional development rhetoric and geopolitical divides, this book creates a common narrative for fostering an equitable global society. This book goes beneath the general development rhetoric, exploring the underlying dynamics of African-European societies, their local practices, and cultures. It also critically examines the post-pandemic global health architecture and the energy crisis from an African-European perspective. Additionally, it includes a dedicated chapter on the influential role of culture in shaping African-European relations.